Renal impairment and its impact on clinical outcomes in patients who are critically ill with COVID‐19: a multicentre observational study. (16th October 2020) - Gasparini, M.; Khan, S.; Patel, J. M.; Parekh, D.; Bangash, M. N.; Stϋmpfle, R.; Shah, A.; Baharlo, B.; Soni, S.
Summary: Renal impairment is common in patients who are critically ill with coronavirus disease‐19 (COVID‐19). We examined the association between acute and chronic kidney disease with clinical outcomes in 372 patients with coronavirus disease‐19 admitted to four regional intensive care units between 10 March 2020 and 31 July 2020. A total of 216 (58%) patients presented with COVID‐19 and renal impairment. Acute kidney injury and/or chronic kidney disease was associated with greater in‐hospital mortality compared with patients with preserved renal function (107/216 patients (50%) (95%CI 44–57) vs. 32/156 (21%) (95%CI 15–28), respectively; p < 0.001, relative risk 2.4 (95%CI 1.7–3.4)). Mortality was greatest in patients with renal transplants (6/7 patients (86%) (95%CI 47–100)). Mortality rates increased in patients with worsening renal injury according to the Kidney Disease: Improving Global Outcomes classification: stage 0 mortality 33/157 patients (21%) (95%CI 15–28) vs. stages 1–3 mortality 91/186 patients (49%) (95%CI 42–56); p < 0.001, relative risk 2.3 (95%CI 1.7–3.3). Survivors were less likely to require renal replacement therapy compared with non‐survivors (57/233 patients (24%) vs. 64/139 patients (46%), respectively; p < 0.001, relative risk 1.9 (95%CI 1.4–2.5)). One‐fifth of survivors who required renal replacement therapy acutely in intensive care continued to require renal support following discharge. Our data demonstrate that renal impairment in patients admitted to intensive care with COVID‐19 is common and is associated with a high mortality and requirement for on‐going renal support after discharge from critical care. Our findings have important implications for future pandemic planning in this patient cohort.